Bioactive food as dietary interventions for liver and gastrointestinal disease - Watson, Ronald R. (Ronald Ross); Preedy, Victor R. (Bioactive foods in chronic disease states., 2013)
Optimum functioning of the liver in conjunction with the gastrointestinal system is critical for health. They are critical for the digestion and absorption of nutrients and foods to produce growth. Nutrients and non-nutrients are important modulators of the liver function. The symptoms related to liver dysfunction include both physical signs and symptoms of abnormal absorption of fat, changes in blood sugar, and altered metabolism. Bioactive Food as Dietary Interventions for Liver and Gastrointestinal Disease provides evidence that foods and their compounds can modify some liver and gastrointestinal diseases.